2017
DOI: 10.1002/adfm.201604811
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Grain‐Boundaries‐Assisted Bipolar and Threshold Resistive Switching in Multilayer Hexagonal Boron Nitride

Abstract: The use of two dimensional (2D) materials to improve the capabilities of electronic devices is a promising strategy that has recently gained much interest in both academy and industry. While the research on 2D metallic and semiconducting materials is well established, the knowledge and 2 applications of 2D insulators are still very scarce. In this report we study the presence of resistive switching (RS) in multilayer hexagonal boron nitride (h-BN) using different electrode materials, and we engineer a family o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
286
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 268 publications
(295 citation statements)
references
References 62 publications
7
286
2
Order By: Relevance
“…A Cu substrate was introduced in a tube furnace, and a three-step growth process was followed: (i) the sample was annealed at 1000 °C under 10 sccm hydrogen atmosphere during 30 min for cleaning its surface; (ii) then the temperature was reduced to 750 °C and a mix of borazine (B 3 N 3 H 6 ) and hydrogen was introduced in the tube in a ratio 2/200 sccm during 10 min; and (iii) the sample was cooled down naturally. [26]. [53].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Cu substrate was introduced in a tube furnace, and a three-step growth process was followed: (i) the sample was annealed at 1000 °C under 10 sccm hydrogen atmosphere during 30 min for cleaning its surface; (ii) then the temperature was reduced to 750 °C and a mix of borazine (B 3 N 3 H 6 ) and hydrogen was introduced in the tube in a ratio 2/200 sccm during 10 min; and (iii) the sample was cooled down naturally. [26]. [53].…”
Section: Methodsmentioning
confidence: 99%
“…The small current fluctuations in Figure 2 should be related to trapping/ de-trapping effects in the h-BN stack, preferably at the GBs of the h-BN stack. [26] On the contrary, the small current steps marked as (3) in Figure 3b are an obvious sudden event (the sampling time in Figures 2 and 3 was the same) but, since it is too small to correspond to a t ox thinness of 0.3 nm, the only feasible explanation is a lateral propagation (in-plane defect formation).…”
Section: Wwwadvelectronicmatdementioning
confidence: 96%
See 1 more Smart Citation
“…The SiO 2 /Si wafer should be covered with a metallic film as BE (the recommended thickness is >50 nm to withstand the high current densities in LRS). [63] It should be noted that (ultimately) the use of industry-compatible conductive alloys (TaN, TiN) is desired, although controlling the amount of oxygen may be challenging in laboratories of several universities and research institutes (in such case, using noble metals may lead to better quality interfaces). The use of noble metals (Au, Pt) as BE is more common than metals that can easily oxidize (Ti, Cu)-and recommendable when working in university labs without exhaustive air and humidity control-because they collect less oxygen from the atmosphere during the time between BE and RS medium deposition (although in the industry noble metals may not be used due to their high cost and etching issue).…”
Section: Selecting the Bottom Electrodementioning
confidence: 99%
“…As shown in Figure 5a,b, Cu/bi-layer MoS 2 /Au memristive devices show low SET (0.25 V) and RESET (−0.15 V) voltages, [112] while the filament formation might be attributed to Cu 2+ diffusion through MoS 2 . [118] By pushing the thickness of active layer to atomic limit, Ge et al reported the first atomristor based on monolayer TMDs (i.e., MoS 2 , MoSe 2 , WS 2 , WSe 2 ). This issue could be surmounted by the use of insulating h-BN [117] as active layer.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%